A competition in unsupervised color image segmentation. (September 2016) - Haindl, Michal; Mikeš, Stanislav
Abstract: A competition in unsupervised color image segmentation took place in conjunction with the 22nd International Conference on Pattern Recognition (ICPR 2014). It aimed to promote evaluation of unsupervised color image segmentation algorithms using publicly available data sets, and to allow for any subsequent methods to be easily evaluated and compared with the results of the contested methods under identical conditions. Our comparison of different methods is based on the standard methodology of performance assessment using an on-line verification server. We present in this paper the evaluation of the top six results submitted to the ICPR 2014 contest in unsupervised color image segmentation and compare them with 11 other state-of-the-art unsupervised image segmenters. Abstract : Highlights: We proposed an unsupervised color image segmentation benchmarking scheme. We present a comparison of leading unsupervised image segmenters. World-wide contest took place in conjunction with the 22nd International Conference on Pattern Recognition (ICPR 2014). The contest uses the online Prague segmentation benchmarkhttp://mosaic.utia.cas.cz .